Learning Management Challenges and Priority Needs for Career Skills Development in Educational Opportunity Expansion Schools - Patcharin Thamchanya; Pacharawit Chansirisira; Xiangrong Liao (Bumi Publikasi Nusantara, 2027)
This study examined learning management challenges and priority needs for career skills development in Educational Opportunity Expansion Schools under the Office of the Basic Education Commission. The sample consisted of 327 respondents selected through multi-stage sampling. Data were collected using a questionnaire whose content validity was evaluated by five experts using the Item-Objective Congruence index. The data were analysed using frequency, percentage, mean, standard deviation, and the Modified Priority Needs Index. The current condition of learning management for career skills development was at a moderate level, while the desired condition was at the highest level. The highest priority need was learning management for career skills, followed by curriculum development and collaboration in learning management.